2014
DOI: 10.1186/s13071-014-0599-y
|View full text |Cite
|
Sign up to set email alerts
|

Anopheles gambiae salivary protein expression modulated by wild Plasmodium falciparum infection: highlighting of new antigenic peptides as candidates of An. gambiae bites

Abstract: BackgroundMalaria is the major parasitic disease worldwide caused by Plasmodium infection. The objective of integrated malaria control programs is to decrease malaria transmission, which needs specific tools to be accurately assessed. In areas where the transmission is low or has been substantially reduced, new complementary tools have to be developed to improve surveillance. A recent approach, based on the human antibody response to Anopheles salivary proteins, has been shown to be efficient in evaluating hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 86 publications
0
17
0
Order By: Relevance
“…TRIO protein is one of several antigenic proteins, in addition to gSG6, gSG1b, SG5, and long form D7, that are over expressed in salivary glands infected with Plasmodium falciparum. Therefore, TRIO proteins may be involved in malaria transmission and may represent a new candidate biomarker for infected Anopheles bites (25) .…”
Section: Immunogenic Proteins Found In Anopheles Sundaicus Salivary Gmentioning
confidence: 99%
“…TRIO protein is one of several antigenic proteins, in addition to gSG6, gSG1b, SG5, and long form D7, that are over expressed in salivary glands infected with Plasmodium falciparum. Therefore, TRIO proteins may be involved in malaria transmission and may represent a new candidate biomarker for infected Anopheles bites (25) .…”
Section: Immunogenic Proteins Found In Anopheles Sundaicus Salivary Gmentioning
confidence: 99%
“…Consistent with this, we detected AgTRIO protein in the salivary glands (Figure 2B). The presence of P. berghei sporozoites in the salivary glands augmented the expression of AgTRIO (Figure 2C) (Marie et al, 2014; Zocevic et al, 2013) and the production of AgTRIO protein (Figure 2D). In addition, AgTRIO was secreted into saliva, as confirmed by a western blot with AgTRIO antiserum (Figure 2E).…”
Section: Resultsmentioning
confidence: 94%
“…We now call it A. gambiae TRIO (AgTRIO) to reflect that it is from A. gambiae , although functional domains required for Rho GTPase activity are lacking. AgTRIO was previously reported to be expressed in the salivary glands of female anopheline mosquitoes (Arca et al, 2005; Marie et al, 2014). We also found that AgTRIO was expressed only in salivary glands and not in other organs (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…The invasion of vector's salivary gland by pathogens causes disturbances in the cells homeostasis, leading to not only activation of the tissue remodeling machinery [22,23], but also modulations in the expression of salivary proteins [20,2226]. The later can have a significant impact in the pathogen transmission.…”
Section: Effects Of Environmental Factors and Pathogens In The Expresmentioning
confidence: 99%
“…Whereas Plasmodium falciparum invasion of the mosquito An. gambiae salivary glands leads to up-regulation in the expression of the gSG6 salivary protein [26], P. berghei invasion in the same vector leads to reduction in the expression of gSG6 and other three secreted proteins (apyrase, D7-related 1, and AEDA), and up-regulation of the protein gVAG [20]. Although infection with DENV-2 virus does not seem to induce differential expression in salivary gland genes encoding secreted proteins in the mosquitoes Ae.…”
Section: Effects Of Environmental Factors and Pathogens In The Expresmentioning
confidence: 99%